2008
DOI: 10.2174/157488808786734015
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Cardiac Disease: Where are We Going?

Abstract: During the last 10 years we have witnessed the development of a new field in research termed Stem Cell Therapy. Classically, it was considered that cells had a limited division and differentiation ability; however, this dogma was challenged when new exciting results about cell multi/pluripotency were presented to the scientific community. It was found that cells from one adult tissue source were able to originate cells of a very different type. The possibility of transplanting these cells into damaged organs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 119 publications
0
7
0
1
Order By: Relevance
“…However, further examination of these improvements revealed that very few stem cell-derived cells were actually incorporated long-term into the tissues of interest. It is now well appreciated that stem cells secrete paracrine factors which have a trophic, cell protective effect on extant tissue cells, and much of the improved tissue functionality in disease models can be attributed to this effect, rather than new cells from the stem cells (Zandonella, 2005; Caplan and Dennis, 2006; Gnecchi et al, 2008; Pelacho and Prosper, 2008; Uccelli et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…However, further examination of these improvements revealed that very few stem cell-derived cells were actually incorporated long-term into the tissues of interest. It is now well appreciated that stem cells secrete paracrine factors which have a trophic, cell protective effect on extant tissue cells, and much of the improved tissue functionality in disease models can be attributed to this effect, rather than new cells from the stem cells (Zandonella, 2005; Caplan and Dennis, 2006; Gnecchi et al, 2008; Pelacho and Prosper, 2008; Uccelli et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Their capacity for differentiation has made stem cells outstanding candidates for the treatment of degenerative diseases, substituting for cells lost during the course of the disorder. Consequently, cardiac diseases and MI have been the object of intense research [5]. Among the cell types studied, mesenchymal stem cells (MSCs) are strong candidates for success in the MI setting.…”
Section: Introductionmentioning
confidence: 99%
“…Among the diversity of sources (reviewed in [2,3]), adipose tissue has become one of the most attractive not only due to its regenerative potential but also for other more practical reasons. Free of ethical, oncological, and immunological concerns present in pluripotent cells (embryonic stem cells or induced pluripotent stem cells (iPS)), adipose tissue stem cell obtention lacks the painful and time-consuming process associated with cells from other sources as skeletal muscle, bone marrow, or heart.…”
Section: Introductionmentioning
confidence: 99%